PERCEPTION OF QUALITY TEACHING FROM THE PERSPECTIVE OF SATISFACTION OF STUDENTS OF THE FACULTY OF MATHEMATICS USING MULTIVARIATE METHODS - Solano Dávila, Olga (2012)
In the present work, determined the most important factors in the perception of the quality of teaching from the perspective of student satisfaction of the Faculty of Mathematics at the National University of San Marcos, using factor analysis (Johnson y Wichern, 1992). It is considered a modification of the scale of measuring the quality of SERVQUAL adapted to measure the quality of teaching. The final survey was conducted during the period from the first to June 15, 2012 with the application of the instrument to students enrolled in the second to tenth cycle Semester 2012-1. To calculate the sample size used stratified random sampling (Scheffer y Mendenhall, 2007) with a limit for the estimation error of 4,5 % and the information provided by the Academic Board of the Faculty of Mathematics, the students were randomly selected to complete the same sample size to 303.